Claire Hopley: New England Cooking - Davidson, Alan (Petits Propos Culinaires, 2024)
Claire Hopley: New England Cooking: Berkshire House, Lee, Mass., 2001: ISBN 1-58157-052-X: 243 pp., b&w photos, p/b, $24.95.